Strengthening Women-Led Institutions and Networks in Africa (African Journal of Public Administration & Management, 2026)
Africa stands at a critical juncture. While we have made huge progress in democracy and development, persistent challenges weak institutions, corruption, and discriminatory policies continue to hinder sustainable development, especially in our rural settings.The African proverb says, "If you want to go quickly, go alone. If you want to go far, go together." For generations, African women have understood this deeply. They have been the backbone of our economies, the custodians of our cultures, and the silent engines of our communities.